Case Report: Botulinum Toxin-A for Complication of Exposure Keratopathy Following Frontalis-Orbicularis Oculi Muscle Flap Shortening - Lai, Chun-Chieh; Lin, Chia-Chen (Frontiers in Medicine, 2022)
Background Lagophthalmos with exposure keratopathy is a potential vision-threatening complication following surgery for blepharoptosis. We report three cases successfully treated with botulinum toxin-A (Botox®, Allergan, Irvine, USA) for this complication. Cases Three patients presented with severe blepharoptosis after surgery for orbital and frontal base tumors. They obtained good appearances after frontalis-orbicularis oculi muscle (FOOM) flap shortening. However, exposure keratopathy developed after the surgery despite frequent use of topical lubricants and autologous serum eye drops. We injected 5-10 units of botulinum toxin-A around the central supra-brow area, which was near the origin of the FOOM flap. One week later, they developed ptosis and could close the eye completely. The corneal defect gradually resolved. They recovered from ptosis 3 months later and never required a second injection. Observations Lagophthalmos with exposure keratopathy is a potential vision-threatening complication following FOOM flap surgery. In severe cases, surgical revision should be considered to partially or totally release the FOOM flap attachment, which also decreases its function permanently. In this case series, we demonstrated that injecting botulinum toxin-A may be a promising method to manage this complication without permanently affecting the function of the FOOM flap. Conclusions A botulinum toxin-A injection may be an effective treatment for patients developing exposure keratopathy after FOOM flap surgery.